2013
DOI: 10.1007/s00216-013-6909-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of comet assay parameters for estimation of genotoxicity by sum of ranking differences

Abstract: Genotoxic potential of waters in six rivers and reservoirs from Serbia was monitored in different tissues of chub (Squalius cephalus L. 1758) with the alkaline comet assay. The comet assay, or a single cell gel electrophoresis, has a wide application as a simple and sensitive method for evaluating DNA damage in fish exposed to various xenobiotics in the aquatic environment. Three types of cells, erythrocytes, gills and liver cells were used for assessing of DNA damage. Images of randomly selected cells were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…As shown in Figure 1C, the comet measurements and statistics used to estimate DNA damage in the cells were exported as a spreadsheet. From the several parameters reported by the software, tail DNA was selected because it covers the widest range of damage and exhibits a linear relationship with DNA double-strand breaks (DSBs) 12 . Outlier comets were deleted from the statistical analysis to decrease the number of false positives, and therefore only 10-25 cells per sample were calculated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 1C, the comet measurements and statistics used to estimate DNA damage in the cells were exported as a spreadsheet. From the several parameters reported by the software, tail DNA was selected because it covers the widest range of damage and exhibits a linear relationship with DNA double-strand breaks (DSBs) 12 . Outlier comets were deleted from the statistical analysis to decrease the number of false positives, and therefore only 10-25 cells per sample were calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Three measures of DNA migration are commonly used: the tail length; olive tail moment (OTM), calculated as a product of the tail DNA% and tail length; and tail DNA%. 12 In this study, all comet assay parameters, including the tail area, tail DNA, tail DNA%, tail length, comet length, and OTM, were analyzed using OpenComet analysis software. Although OTM appears to be the most statistically significant measurement, inter-laboratory results are difficult to compare because a standard unit has not been set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high concentrations used in our cell culture studies represent a limitation of the present study since they are clearly far above the concentration range that can be achieved in rodents and patients [26]. In addition, there is ongoing discussion on the application of the Comet assay, which can be evaluated by DNA migration (tail moment) [54] or by the tail intensity (used in the present study), which both are considered reliable Comet assay parameters for estimation of genotoxicity [56].…”
Section: Etohmentioning
confidence: 92%
“…Although organic extracts of domestic wastewaters can be genotoxic, their potency is several folds below those of many industrial wastewaters [57]. In our previous study performed on Squalius cephalus in the Kolubara River basin, we have observed noteworthy genotoxic pollution [58,59].…”
Section: Genotoxicity Assessment: In Situ Assessmentmentioning
confidence: 99%